Comparison between Sleeve Gastrectomy and One-Anastomosis Gastric Bypass in Terms of Weight Loss in Morbidly Obese Patients - Abubaker Khattak; Saeed Sarwar; Rehan Saeed; Muhammad Amin Khan; Nida Ahmad; Waleed Ahmad (Indus Journal of Bioscience Research, 2025)
Background: Morbid obesity presents a significant public health concern, necessitating effective surgical interventions for sustained weight loss. One-anastomosis gastric bypass and sleeve gastrectomy are commonly performed bariatric procedures, yet their comparative short-term outcomes continue to be investigated. This study aimed to evaluate and compare postoperative weight loss in patients undergoing OAGB versus SG. Objective: To compare sleeve gastrectomy with one-anastomosis gastric bypass in terms of weight loss in patients with morbid obesity. Study Design: Prospective Cohort Study. Duration and Place of Study: This study was conducted from May 2024 to January 2025 in the Department of Surgery, Khyber Teaching Hospital, Peshawar. Methodology: A total of 146 patients aged 30–50 years with BMI >35 kg/m² were enrolled and allocated into two equal groups (OAGB and SG, n=73 each) through non-probability consecutive sampling. Patients with comorbidities or medication use that could confound weight loss were excluded. All procedures were performed by experienced surgeons, and patients were followed for six months. Postoperative BMI and weight were measured, and total weight loss (TWL) was analyzed. Results: The mean age and preoperative BMI were similar between groups. At six months, the OAGB group had significantly lower BMI (35.75±2.71 kg/m²) compared to the SG group (36.93±2.86 kg/m²; p=0.012). BMI reduction was more pronounced in males, patients aged >40 years, and rural residents undergoing OAGB. Conclusion: OAGB is more effective than SG in achieving short-term BMI reduction in morbidly obese patients, particularly among older and male populations, indicating its potential as a preferred surgical option in selected cases.